Hormones, feeding and animal models - le Roux, Carel (Henry Stewart Talks, 2015)
The role of hormones in appetite regulation, Surgical principles of gastric bypass and gastric banding, Animal models of gastric surgery, Postoperative weight loss and food intake, Postoperative changes in food preference, Postoperative changes in gut microbiota